Platelet inhibition strategies in rescue stenting after failed thrombectomy: a large retrospective multicenter registry - Aikaterini Anastasiou; Alex Brehm; Johannes Kaesmacher; Adnan Mujanovic; Marta de Dios Lascuevas; Tomás Carmona Fuentes; Alfonso López-Frías; Blanca Hidalgo Valverde; Ansgar Berlis; Christoph J. Maurer; Thanh N. Nguyen; Mohamad Abdalkader; et al. (Therapeutic Advances in Neurological Disorders)
Background: Rescue stenting (RS) is a bailout strategy for failed thrombectomy. Optimal platelet inhibition strategy after RS remains unclear. Objectives: We aimed to describe and compare different platelet inhibition strategies during/after RS. Design: Retrospective cohort study across 34 international centers. Methods: Patients with large vessel occlusion and RS after failed thrombectomy (2019–2023) were included. Periprocedural and postprocedural platelet inhibition strategies were described and compared, focusing on glycoprotein IIb/IIIa (GPIIb/IIIa) inhibitors, single antiplatelet therapy (SAPT), and dual antiplatelet therapy (DAPT). We assessed the effects of platelet inhibition strategy and potentially covariates on the primary outcome of 90-day modified Rankin Scale (mRS) using ordinal shift analysis with proportional odds models. Results: RS was performed in 589 patients (mean age 67.9 years, 60.8% male). Numerous combinations of platelet inhibitors were administered. Periprocedural GPIIb/IIIa inhibitors were used in 61.5% of patients. Postprocedural DAPT was administered to 80.5% and SAPT to 13.3%. Functional independence (mRS 0–2) was achieved in 40.7%, while 26.3% died within 90 days. Stent occlusion occurred in 20.5%, with 67.6% of these occlusions within 24 h. Postprocedural stent-occlusion was independently associated with worse functional outcome at 90 days (OR 4.1, 95% CI 2.3–7.2, p  < 0.001). No significant association between periprocedural GPIIb/IIIa inhibitors, and 90-day mRS or stent occlusion was found. Postprocedural SAPT was associated with worse functional outcomes (adjusted odds ratio (aOR) 2.4, 95% CI 1.1–5.0, p  = 0.02), higher mortality (aOR 2.1, 95% CI 1.05–4.0, p  = 0.03), and increased stent occlusion rates (aOR 4.8, 95% CI 2.3–9.7, p  < 0.001) compared to postprocedural DAPT. Symptomatic intracranial hemorrhage occurred in 6.8% of patients, with no significant difference between antiplatelet regimens. Conclusion: Extensive heterogeneity exists in platelet inhibition strategies following RS. Stent occlusion is associated with worse clinical outcomes, and the first 24 h post-RS are critical for stent patency. Compared to SAPT, DAPT was associated with better functional outcome, lower mortality, and lower stent occlusion rates.